Energy-dispersive spectroscopy for the quantitative determination of the major chemical elements in milk (Research, Society and Development, 2021)
The present preliminary study aims at the rapid quantitative determination of the major chemical elements in the ashes of raw milk samples, using energy dispersive X-ray fluorescence spectrometry. The precision of the method was satisfactory (variation coefficient ≤ 5%). The mean values (in mmol·kg-1) obtained from the analysis of 32 raw milk samples showed good agreement with data from the Brazilian and international literature: K (26.1 ± 4.6), Ca (33.8 ± 3.7), P (28.4 ± 2.7), Na (21 ± 3.3) and Mg (4.7 ± 0.5). Residual Cl concentration (19.0 ± 3.3 mmol·kg-1) was lower than expected due to incineration losses. The results suggest a good application potential of the method for other dairy products.